The Impact of Customer Experience and Customer Delight on Customer Loyalty of Tokopedia Platform at IBA Student - Joshua Samuel Wangania; S.L.H.V. Joyce Lapian; Regina Trifena Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
This research has purpose to analyze the impact of customer experience and customer delight on customer loyalty of tokopedia platform. The sample of this research is 112 respondents were collected with questionnaire distributed via social medias from IBA students batch 2018-2020 faculty of economics & business in University of Sam Ratulangi. This research used quantitative method. Data analysis used Multiple Linear Regression analysis method conducted by using SPSS 25 version software. The results of this research show that customer experience and customer delight on customer loyalty. Customer experience has a positive relationship and has a significant impact on customer loyalty. While customer delight has a negative relationship and significant impact on customer loyalty of tokopedia platform on IBA students batch 2018-2020.